Thermo-optical properties of polymer planar waveguides / Mohd Kamil Abd Rahman ... [et al.] - Abd Rahman, Mohd Kamil; Kassir, Aiman; Ehsan, Abang Annuar; Razali, Noraspalelawati; Shaari, Sahbudin (Faculty of Applied Sciences, 2005)
The variation of refractive indices with temperature in polymer waveguides on silicon substrate is presented. The refractive index n, thickness and birefringence properties of the material has been studied in the temperature range of 40 °C to 80 °C. An apparent reduction of the refractive index with increase of temperature of the material was observed, while there was no significant thickness-variation with temperature in the film coating. This behavior may be attributed to the heat activate orientation mobility of the atoms of the polymer. The polarization anisotropy results are consistent with that would be expected of the transverse electric, TE and transverse magnetic, TM modes. The refractive index and thickness were examined as a function of spin coating parameter of the polymer. Temperature induced changes in nTE and nTM were studied for different planar waveguides parameters. The measured dn/dT coefficient of the polymer material matches with the standard value.